Solid-state NMR characterization of the structure and thermal stability of hybrid organic–inorganic compounds based on a HLaNb2O7 Dion–Jacobson layered perovskite. Issue 31 (21st July 2016) - Cattaneo, Alice S.; Ferrara, Chiara; Marculescu, Adriana Mossuto; Giannici, Francesco; Martorana, Antonino; Mustarelli, Piercarlo; Tealdi, Cristina
Abstract : Hybrids obtained via intercalation of alkylamines or propanol show peculiar structure and thermal stability, which are influenced by the nature and the amount of the intercalated chains. Abstract : Dion–Jacobson phases, like MLaNb2 O7, are an interesting class of ion-exchangeable layered perovskites possessing electronic and photocatalytic properties. Their protonated and organo-modified homologues, in particular, have already been indicated as promising catalysts. However, the structural analysis of these highly tailorable materials is still incomplete, and both the intercalation process and thermal stability of the included organic moieties are far from being completely understood. In this study, we present a thorough solid-state NMR characterization of HLaNb2 O7 · x H2 O intercalated with different amounts of octylamine, or with decylamine. Samples were analyzed as prepared, and after thermal treatment at different temperatures up to 220 °C. The substitution of pristine proton ions was followed via 1 H MAS NMR spectroscopy, whereas the alkyl chains were monitored through 13 C( 1 H) CP MAS experiments. The interactions in the interlayer space were explored using 13 C( 1 H) 2D heteronuclear correlation experiments. We demonstrate that some of the protons are involved in the functionalization reaction, and some of them are in close proximity to the alkyl ammonium chains. Heating of the hybrid materials leads first to a rearrangement of the alkyl chains and then to their degradation. The spatial arrangement of the chains, their interactions and the thermal behavior of the materials depend on the extent of the functionalization, and on the nature of the intercalated alkyl ammonium ions.